Estudio de clima laboral e implementación de planes de mejora para el área de secretaria de la Universidad Politécnica Salesiana sede Quito - Coba Paz, Daniela Paulina (2015)
The objective of this project is to measure working environment and implementation of improvement plans in the area of secretary of the Universidad Salesiana Politécnica campus Quito. For this project has been divided into four chapters. In chapter I approach the theoretical content, making a historical tour of changes in the organization and the different theories of motivation and definitions of Work climate based on some authors, revealing its importance within the organizational environment. In chapter II, defined population and sample that will be carried out the measurements and improvement plans, based on general and specific institutional framework of the Universidad Salesiana. In chapter III, the measurement procedure Working Environment, which contains the schedule, communication plan, description of the tool, application, tabulation, analysis of results and conclusions were developed. According to the analysis and research tools to assess the Employee Satisfaction within the area secretary, has decided to use the CLA (Cuestionario Clima Laboral) for its validity and approval worldwide. In chapter IV, based on the analysis in Chapter III we develop improvement plans and implementation guidance focused on variables that focuses the CLA questionnaire planned short and medium term, same to be implemented by the Department of Human Talent together with the Secretary area.